Strategic alliances between SMEs and large firms: An exploration of the dynamic process - Senad Rothkegel; Ljiljana Erakovic; Deborah Shepherd (Management Revue, 2006)
This paper explores the dynamics in strategic alliances between small and medium sized enterprises (SMEs) and large organisations (corporates). Despite the volumes written on this subject, few studies take into account this context of interorganisational relationships. The dynamics in strategic partnerships between small and large organisations are potentially multifaceted and fraught with complexities and contradictions. The partner organisations bring diverse interests and resources to the strategic partnerships and these affect the dynamics of their relationships. Using the literature on strategic alliances, this article examines four such strategic partnerships in New Zealand. Results show that in order to increase the likelihood of successful collaboration, the alliance partners must understand the importance of building trust and a shared alliance purpose, and both of these must be communicated effectively at executive and operational levels.
Keywords: 650; strategic alliances; SMEs; trust; commitment; New Zealand; Strategische Allianz; KMU; Großunternehmen; Neuseeland